Comparison of clinical outcomes in critical patients undergoing different mechanical ventilation modes: a systematic review and network meta-analysis - Wu, Mengyu; Zhang, Xiaohong; Jiang, Yu; Guo, Yun; Zhang, Wenjing; He, Hong; Yin, Yanhua (Frontiers in Medicine, 2023)
Purpose: To evaluate the effects of different mechanical ventilation modes on critical patients. Methods: PubMed, Embase, Web of science, and Cochrane Library databases were searched from their inception to November 15, 2022 for randomized controlled trials on the application of different mechanical ventilation modes in critical patients. Two researchers independently screened the literature, extracted data, and assessed the risk of bias in the included studies. R4.2.1 was used for this network meta-analysis. Results: Twenty-eight RCTs involving 3,189 patients were included. The interventions in these RCTs included NAVA (Neurally adjusted ventilatory assist), PAV (proportional assist ventilation), ASV (adaptive support ventilation), Smartcare/PS (Smartcare/pressure support), PSV (pressure support ventilation), PSV_ATC (pressure support ventilation_ automatic tube compensation) and SIMV (Synchronized Intermittent Mandatory Ventilation). The network meta-analysis showed that, compared with the PSV group, there was no significant difference in duration of mechanical ventilation, duration of ICU stay, and hospital stay between NAVA, SIMV, AVS, PAV, Smartcare/PS, and PSV_ATC groups. Compared with PSV, PAV improved the success rate of withdrawal of ventilator [OR=3.07,95%CI(1.21,8.52)]. Compared with PSV and PAV, NAVA reduced mortality in the ICU [OR=0.63,95%CI(0.43,0.93); OR=0.45,95%CI(0.21,0.97)]. Conclusions: NAVA can reduce mortality in ICU, and PAV may increase the risk of withdrawal of the ventilator. There was no significant difference between PSV and other mechanical ventilation modes (NAVA, SIMV, AVS, PAV, Smartcare/PS, and PSV_ATC) in the duration of mechanical ventilation, duration of ICU stay, or hospital stay. Due to the limitations, more high-quality studies are needed to verify these findings.